Emotions Guaranteed: On the Kitsch Contract - Thomas Küpper (ESPES)
Kitsch is usually described as overwhelming – as if it captivates the audience, almost inevitably taking hold of them and manipulating emotions. Such assumptions are influenced by aesthetic positions like Kant’s, who claimed that ‘pure’ aesthetic judgments are independent of emotions, a position out of which a traditional defensive attitude towards emotions in the aesthetic sphere emerged. While steadfast in this defensiveness towards kitsch, the question arises whether theories in this lineage have not in fact overestimated the directness and completeness of kitsch’s effect on and power over the audience. The paper argues that emotionalizing kitsch is based on a more complex set of presuppositions: for kitsch to function at all, a contract with the audience is required, the audience granting kitsch the right to temporarily steer their feelings, a means that allows them to – paradoxically – still maintain a hold over their loss of control.